Long-term verification of signatures based on a blockchain. (January 2020) - Hyla, Tomasz; Pejaś, Jerzy
Abstract: Digitally signed documents must remain stored for many years. In this paper, a scheme that would allow maintaining signature validity without the necessity to use timestamps from trusted third parties is proposed. According to the scheme, after inserting data into a blockchain, a user can store a signed document in his storage without the need to perform any maintenance actions in the future. The Round-based Blockchain Time-stamping Scheme is proposed that is scalable, i.e., it requires embedding a constant number of bytes into a blockchain independent from a number of input documents. The scheme allows to prove that a document existed not only before a certain date, but after a certain date as well. Moreover, the purpose of the scheme is to meet non-repudiation requirements for digitally signed documents. The scheme allows verifying signature validity using a chain model and under some conditions using a modified shell model.